An Episodic Model of Power: Toward an Integration of Theory and Research - Cobb, Anthony T. (Academy of Management Review, 1984)
The concept of power has long occupied a place of importance in the organizational literature. Despite this attention, or perhaps because of it, just how the concept should be viewed and used in social analysis has engendered scholarly division and controversy. The concept of power is reexamined here, with past work integrated into an episodic model of power.